Understanding Success: A Constructionist Approach to Identifying Success Factors Among the Polish Entrepreneurs Using Polish Panel Survey (POLPAN), 1988-2018 - Yevhen REVTIUK; Olga ZELINSKA (Communications of International Proceedings, 2020)
In this initial investigation we took the constructionist stance attempting to enhance the scholarly community’s understanding of how Polish entrepreneurs construct own success factors and if this has changed over time, as the country transited from command to market economy. Using the data from the Polish Panel Survey, POLPAN, waves 1988-2018, we were able to identity “Social Capital”, “Luck” and the “Need for achievement” as the main factors which entrepreneurs believed contributed to their success. At the same time, we were able to demonstrate that the way entrepreneurs construct own success factors has changed during Poland's transit.
Keywords: Entrepreneurship; Success; Constructionism; POLPAN; Poland